Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T13:25:30+01:00
Log o podstawie 0,5 z 56 - log o podstawie 0,5 z 7 - 1= log o podstawie 0,5 z 56/7 - 1 = log o podstawie 1/2 z 8 - 1 = -6-1 = -7

2 + log o podstawie 9 z 7 - log o podstawie 9 z 21 = 2 + log o podstawie 9 z 7/21 = 2 + log o podstawie 9 z 1/3 = 2 - 1/2 = 3/2
1 3 1
2010-03-04T13:42:57+01:00
A)
log ₀,₅ 56 - log ₀,₅ 7 - 1= log½ (56 /7) - log½ (1/2) =
= log½ 8 - log ½ (1/2) = log ½(8:½) = log ½ 16 = -4
bo (1/2)⁻⁴ = 2⁴ = 16
b)
2 + log ₉ 7 - log ₉ 21 = log ₉ 81 + log ₉ (7/21) =
= log ₉ 27 = 3/2 ,
bo √9³ = √ 729 = 27